Liraglutide, a GLP-1 Receptor Agonist, Which Decreases Hypothalamic 5-HT2A Receptor Expression, Reduces Appetite and Body Weight Independently of Serotonin Synthesis in Mice - Katsunori Nonogaki; Takao Kaji (Journal of Diabetes Research)
A recent report suggested that brain-derived serotonin (5-HT) is critical for maintaining weight loss induced by glucagon-like peptide-1 (GLP-1) receptor activation in rats and that 5-HT2A receptors mediate the feeding suppression and weight loss induced by GLP-1 receptor activation. Here, we show that changes in daily food intake and body weight induced by intraperitoneal administration of liraglutide, a GLP-1 receptor agonist, over 4 days did not differ between mice treated with the tryptophan hydroxylase (Tph) inhibitor p-chlorophenylalanine (PCPA) for 3 days and mice without PCPA treatment. Treatment with PCPA did not affect hypothalamic 5-HT2A receptor expression. Despite the anorexic effect of liraglutide disappearing after the first day of treatment, the body weight loss induced by liraglutide persisted for 4 days in mice treated with or without PCPA. Intraperitoneal administration of liraglutide significantly decreased the gene expression of hypothalamic 5-HT2A receptors 1 h after injection. Moreover, the acute anorexic effects of liraglutide were blunted in mice treated with the high-affinity 5-HT2A agonist (4-bromo-3,6-dimethoxybenzocyclobuten-1-yl) methylamine hydrobromide 14 h or 24 h before liraglutide injection. These findings suggest that liraglutide reduces appetite and body weight independently of 5-HT synthesis in mice, whereas GLP-1 receptor activation downregulates the gene expression of hypothalamic 5-HT2A receptors.